2020
DOI: 10.1007/s10212-020-00467-4
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers’ evidence-based reasoning during pedagogical problem-solving: better together?

Abstract: This study investigates if collaboration and the level of heterogeneity between collaborating partners' problem-solving scripts can influence the extent to which pre-service teachers engage in evidence-based reasoning when analyzing and solving pedagogical problem cases. We operationalized evidence-based reasoning through its content and process dimensions: (a) to what extent pre-service teachers refer to scientific theories or evidence of learning and instruction (content level) and (b) to what extent they en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 55 publications
1
23
0
2
Order By: Relevance
“…In a study focusing on the potential of (Hendriks, Kienhues & Bromme, 2015) Criteria related to the media Different media per se (e. g., layperson or expert forum) (Zimmermann & Jucks, 2018) Rank of search result in search engine -a search engine's navigability (affordance) (Haas & Unkel, 2017) Other aspects not related to the online information Experiential knowledge sources, such as own teaching experiences (Bråten & Ferguson, 2015) Note: This table represents an excerpt of research studies on criteria shown to be relevant in sourcing online information. collaboration for synthesizing evidence, for example, future teachers who engaged in collaboration analyzed pedagogical problems in a more reflective and evidence-based manner (Csanadi, Kollar & Fischer, 2020). Collaborative engagement also seems to provide a promising setting for sharing, interpreting, and critically examining scientific information in online contexts (Hendriks et al, 2020).…”
Section: The Potential Of Collaborative Argumentation To Foster Critical Reflectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study focusing on the potential of (Hendriks, Kienhues & Bromme, 2015) Criteria related to the media Different media per se (e. g., layperson or expert forum) (Zimmermann & Jucks, 2018) Rank of search result in search engine -a search engine's navigability (affordance) (Haas & Unkel, 2017) Other aspects not related to the online information Experiential knowledge sources, such as own teaching experiences (Bråten & Ferguson, 2015) Note: This table represents an excerpt of research studies on criteria shown to be relevant in sourcing online information. collaboration for synthesizing evidence, for example, future teachers who engaged in collaboration analyzed pedagogical problems in a more reflective and evidence-based manner (Csanadi, Kollar & Fischer, 2020). Collaborative engagement also seems to provide a promising setting for sharing, interpreting, and critically examining scientific information in online contexts (Hendriks et al, 2020).…”
Section: The Potential Of Collaborative Argumentation To Foster Critical Reflectionmentioning
confidence: 99%
“…The dialogic setting can thus stimulate the explicit articulation of dialog partners' ideas by asking them for clarification and critical elaboration on the reasons behind these ideas. It thereby promotes highquality cognitive elaboration processes that are assumed to elicit changes in knowledge structures (Csanadi et al, 2020;Van Boxtel, van der Linden & Kanselaar, 2000). Accordingly, explicit forms of cognitive elaboration processes are often considered indicators for the depth of one's reflection processes (Csanadi et al, 2020;Felton & Kuhn, 2001;.…”
Section: The Potential Of Collaborative Argumentation To Foster Critical Reflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, studies have indicated that, in contrast to individual reflection settings, collaborative reflection settings may be beneficial in order to promote students' elaboration of their own thinking and challenging of the other's idea (Kuhn and Moore, 2015), their elaborated reasoning of their own sourcing strategies (Zimmermann and Mayweg-Paus, 2021), as well as their analysis and reflection of problems (Csanadi et al, 2020). However, in direct comparisons of individual and collaborative communicative settings wherein students engaged in cognitive reasoning processes, dyads have been shown to spend more time and effort than individuals: Collaboration requires time to explain possible causes of a problem (Csanadi et al, 2020); in collaboration there is a risk that some partners may move more quickly through the phases of the collaboration task, before everyone is ready (Mullins et al, 2011); and in collaborative settings, partners spend more time on managing the task (Zimmermann and Mayweg-Paus, 2021).…”
Section: Dealing With Online Scientific Information About Covid-19mentioning
confidence: 99%
“…For evidence-based practice for special educational needs to be properly developed in schools, the literature points towards the need for teachers, both at pre-service and inservice stages, to have opportunities to engage in collaborative problem-based reflective enquiry which allows them to flexibly consider how evidence-based approaches can be individually applied within the local classroom context (Csanadi et al, 2021;Hick et al, 2019b;Mintz et al, 2020Mintz et al, , 2021Russo-Campisi, 2017). At the same time, there is also support in the literature for the potential for teachers with specific training and knowledge in the effective inclusion of children with SEN, and in specific evidence-based practices, to support generalist teacher colleagues in achieving high-quality teaching, including the flexible use of evidence-based approaches, tailored to the needs of individual children (Cochran-Smith and Dudley-Marling, 2012;Fitzgerald and Radford, 2020;Hornby, 2020).…”
Section: Discussionmentioning
confidence: 99%